Uji ketahanan beberapa Varietas Padi Rawa Pasang Surut terhadap Penyakit Tungro di Rumah Kaca - Rudi Tomson Hutasoit; Rini Ismayanti (Seminar Nasional Lahan Suboptimal, 2020)
Hutasoit RT, Ismayanti R.  2020.  Resistance evaluation of several wetland rice varieties to tungro disease in greenhouse condition. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Tungro is one of the important diseases in rice. This disease is caused by multiple infections of the two types of viruses, Rice Tungro Bacilliform Virus (RTBV) and Rice Tungro Spherical virus (RTSV). This study aims to evaluate the resistance of several wetland rice varieties to tungro disease. The varieties tested in this study were Banyuasin, Batanghari, Indragiri, Kapuas, Komojoyo and TN1 as susceptible varieties. The evaluation of these varieties carried out using the test tube method. The disease transmission was carried out on 10 plant seeds of each variety with four replications. The level of resistance were determined based on the severity of tungro symptoms according to the IRRI Standard Evaluation System for Rice. The results showed that the five several wetland rice varieties were categorized as susceptible with a high incidence or percentage of attack 90-100% and a disease index (DI) that varied between varieties. Observations of the incubation period showed that the symptoms of tungro disease appeared fastest in the TN1 varieties, followed by Indragiri, Banyuasin, Batanghari, Kapuas, and Komojoyo.